ANALISIS KESULITAN BELAJAR SISWA TUNANETRA DI KELAS INKLUSIF PADA MATERI TRIGONOMETRI - Pujia Siti Balkist (UJMES (Uninus Journal of Mathematics Education and Science), 2020)
The purpose of this study was to analyze the learning obstacles of blind students in an inclusive class at one of the high schools inSukabumi City as an inclusive schools. The method used is a qualitative method to analyze the learning difficulties of blind studentsin the inclusive class. The learning material that is focused on is trigonometry material which is quite abstract but quite applicable forall students in mathematics subjects. The analysis was carried out by observing the responses of blind students and other students inthe class simultaneously to the learning given to trigonometric material. The results show that learning obstacles of blind students ininclusive class include abstraction difficulties, inappropriate learning trajectory and lack of basic mathematical concepts.